“La gestión administrativa y la satisfacción del cliente en la asociación de comerciantes minorista, Cotopaxi del cantón La Maná año 2022”. - Espín Santillán, María Mercedes (2022)
The present research entitled as: The administrative management and customer satisfaction in the Association of Retail Merchants "Cotopaxi" of Canton La Maná, Year 2022; was carried out with the purpose of making a diagnosis about the administrative management that each of the merchants who sell products to their customers so that they later proceed to make them reach the regular consumer. The relationship between the two main variables of the research is established within the same, achieving the development of an improvement proposal that will ensure customer satisfaction. The main beneficiaries of the research are encompassed in the Association of Retailers "Cotopaxi" which are focused as direct, since they are those who through the proposal will improve their services and the internal administration of their businesses, and on the other hand the customers because they will receive a better service achieving to satisfy their needs as intermediaries of the products. This research was based on administrative management, which is important since the application of this model will fulfill the objectives of the organization and will have an impact on its gradual growth. The field research helped to confirm the acceptance or rejection of the hypothesis of the research where it was possible to obtain as a result that many of the retailers who belong to the association do not have an administrative management model and that a group of clients is not satisfied with the control and organization of products/services received. The main impact of the research was the improvement of the administrative processes of the Association of Retailers "Cotopaxi", which will help members and their businesses to meet their objectives for business development.